2002
DOI: 10.1016/s0010-0277(01)00167-6
|View full text |Cite
|
Sign up to set email alerts
|

The scope of linguistic generalizations: evidence from Hebrew word formation

Abstract: Does the productive use of language stem from the manipulation of mental variables (e.g. "noun", "any consonant")? If linguistic constraints appeal to variables, rather than instances (e.g. "dog", "m"), then they should generalize to any representable novel instance, including instances that fall beyond the phonological space of a language. We test this prediction by investigating a constraint on the structure of Hebrew roots. Hebrew frequently exhibits geminates (e.g. ss) in its roots, but it strictly constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…They hence conclude that 'knowledge of phonotactic constraints is independent from simple lexical statistics ' (2001:104). Berent, Everett and Shimron (2001), Berent, Shimron and Vaknin (2001), and Berent et al (2002) come to a similar conclusion based on word-likeness rating experiments with Hebrew listeners. There is also similar evidence for an independent contribution of grammar to speech processing in other kinds of tasks.…”
Section: On the Relation Between Grammar And Frequencysupporting
confidence: 68%
See 1 more Smart Citation
“…They hence conclude that 'knowledge of phonotactic constraints is independent from simple lexical statistics ' (2001:104). Berent, Everett and Shimron (2001), Berent, Shimron and Vaknin (2001), and Berent et al (2002) come to a similar conclusion based on word-likeness rating experiments with Hebrew listeners. There is also similar evidence for an independent contribution of grammar to speech processing in other kinds of tasks.…”
Section: On the Relation Between Grammar And Frequencysupporting
confidence: 68%
“…Moreton (2002), Pitt (1998), Berent et al (2007), Dupoux et al (2001) and Coetzee (2005) all show that grammar influences perception. Berent, Shimron and Vaknin (2001) and Berent et al (2002) show in a similar manner that grammar influences reaction times in lexical decision. Zuraw (2007) shows that the way in which Tagalog speakers applies a morphological process to nonce words cannot be accounted only by frequency statistics.…”
Section: On the Relation Between Grammar And Frequencymentioning
confidence: 72%
“…Likewise, Hebrew speakers judge a nonce root that starts with two identical, non-native consonants, such as [θ-θ], as less acceptable than an analogous root with non-identical consonants (e.g. [θ-k]), even though both sequences have a frequency of 0 in Hebrew (Berent et al 2002). These results suggest that speakers generalize over attested structures and apply these generalizations to make distinctions among unattested ones.…”
Section: Introductionmentioning
confidence: 88%
“…A large range of studies have shown that such generalizations can be acquired in artificial language studies (Gervain, 2014;Marcus et al, 1999;Moreton, 2012). In natural languages, generalizations that have to do with segment repetition or bans on repetition have been documented in Yucatec Mayan, Hebrew, Peruvian Aymara, and other languages (Berent et al, 2002;Gallagher, 2013).…”
Section: Experiments 2a: a Probabilistic Abstract Generalizationmentioning
confidence: 98%